Factors That Impact College Students' Perceptions of Sexual Pleasure and Satisfaction. Issue 1 (2nd January 2020) - Milstein, Susan; Hilliard, Taylor Elizabeth; Hall, Scott; Knox, David; Hunter, Genevieve
Abstract: It is important to understand how people experience pleasure and sexual satisfaction with a partner, as these phenomena can impact how they view their relationships, themselves, as well as the role of sexual activities within relationships. Three hundred and four undergraduates at East Carolina University and California State University Chico who reported having at least one sexual experience with a partner completed a 45 item survey assessing social correlates of sexual pleasure and sexual satisfaction. Analysis revealed that those in a committed relationship reported the highest sexual pleasure (on average), followed by those in an emotionally-involved relationship, followed by those in a hookup. A parallel analysis for sexual satisfaction revealed the same associations. Regarding the length of relationship, being in a relationship for at least six weeks appeared to matter for pleasure and satisfaction, but being in a relationship longer than six months did not indicate greater advantages than those in a relationship between six weeks and six months. Limitations of the research are identified.